Antagonistic activity of some bacterial and fungal isolates against wheat root pathogens - Kuldybayev, Nurlan; Qairatova, Aigerim; Suleimenova, Zhanar; Dzhakibayeva, Gulnar; Yelubayeva , Akmeiir; Dutbayev, Yerlan (Eurasian Journal of Applied Biotechnology, 2025)
One of the most significant diseases of winter wheat (Triticum aestivum L.) in Kazakhstan is root rot. This study aimed to isolate and identify some rhizosphere microorganisms associated with winter wheat and evaluate their antagonistic activity against root rot pathogens in the southeast region of Kazakhstan. More than 6 bacterial and 4 fungal isolates belonging to the genera Bacillus, Lysinibacillus, Fusarium, Alternaria, and Cladosporium were identified. Identified as Strain K-C- 24 Bacillus mojavensis and collection strains Trichoderma asperellum strains GL and 101 showed the highest antagonistic activity against Bipolaris sorokiniana and Fusarium oxysporum with inhibition zones of 23.5 ± 0.5 mm, and 42 ± 0.5 mm, respectively. Similar activity was not detected in other isolates. In the field, the best antagonistic inhibition rates of these wheat root rot pathogens were found when treated with a consortium of bacteria of the genera Bacillus and Lysinibacillus (Mix bac) and a strain of T. asperellum GL. The secondary metabolites contained in the culture filtrates of Bacillus and Trichoderma strains that inhibit the growth of test pathogens confirm the nature of their antagonism. The results obtained demonstrate the potential of using these antagonist strains, such as T. asperellum, B. mojavensis and a consortium of Bacillus and Lysinibacillus bacteria (a mixture of bac strains), in order to develop safe biological preparations against root rot of spring and winter wheat in the southeastern region of the country.